REVEALING POSTTRAUMATIC GROWTH, IDENTITY AND GLOBAL INFLUENCE IN DEMI LOVATO: DANCING WITH THE DEVIL DOCUMENTARY - Wijaya, Clara Andita Dwi Putri; Munjid, Achmad (Rubikon : Journal of Transnational American Studies, 2024)
As a singer and an actress, Demi Lovato has fame which can influence her fans globally. Further, with the mental health, addiction, and trauma issues, she gains positive changes in her life that affect and encourage her fans as well. The object of this study is Demi Lovato: Dancing with the Devil documentary series. This study reveals Lovato’s posttraumatic growth that influences her identity and global influence. The narratives, captured clips, posts, and previous research are used as the data in this study. This study uses the theory of posttraumatic growth and new media for data interpretation. The findings show that Lovato’s posttraumatic growth consists of five domains: personal strength, relations to others, new possibilities, appreciation of life, and spiritual and existential changes. Moreover, her posttraumatic growth also leads her to discover her identity as a non–binary person and bring positive impacts to her fans around the world and the non-binary community. Therefore, as a new media form, the Dancing with the Devil documentary series successfully delivers Lovato’s stories and struggles to people worldwide, especially her fans.